The study of the KM gaps between personal knowledge management and enterprise knowledge management - Lin, Chen-Chun; Hsieh, Ping-Jung; Shyu, Joseph Z. (My University, 2007)
In recent years, there has been increased emphasis on the importance of knowledge management (KM) in facilitating knowledge workers, enhancing productivity, and increasing business competitiveness. Enterprises also have recognized knowledge workers as a key source of competitive advantage. Therefore, keeping daily work comes to personal knowledge mangement, (PKM), is very important for knowledge workers to get a handle on the amounts of information every day. Hence, major role of enterprise knowledge management (EKM) function services in establishing environment, resource, information and knowledge for knowledge workers executing PKM. PKM and EKM were both proposed to efficiently and effetively acquire knowledge. Due to these reasons above, this article deals with knowledge management gaps between PKM and EKM. Two phase studies are proposed in this study. The first model discusses the influential factors between PKM and EKM. The second phase study further explores if influential factors change into KM gaps between PKM and EKM. This paper will be surveyed by questionnaire. And the data analysis is manipulated by using the statistical methods, including descriptive statistics analysis, internal consistency reliability, student's Nest, chi-square test and factor analysis. The study actually confirmed hypotheses mentioned above. That would mean that the parent organizations should put more efforts in amending knowledge management, especially in technology, structure, and culture KM gaps. Reducing the KM gaps in attributing to improve knowledge management activities fosters knowledge workers to execute PKM, which will eventually result in a more effective and satisfactory accomplishment of knowledge management. The major expected practical implication is the benefit of knowledge workers as a result of better individual work performance in KM activity and in the overall organization KM process.